New Chronicles of Rebecca - Wiggin, Kate Douglas Smith, 1856-1923 (Salt Lake City, UT : Project Gutenberg, 1998)
"New Chronicles of Rebecca" by Kate Douglas Smith Wiggin is a novel written during the early 20th century. It continues the charming adventures of its titular character, Rebecca Randall, a lively and imaginative girl who navigates the challenges of growing up within the constraints of her aunts$1 (Bhome in Riverboro, Maine. The story features her spirited personality as she explores her love for poetry and creative expression while grappling with the realities of life, such as understanding death, friendship, and moral duties. The beginning of "New Chronicles of Rebecca" introduces readers to Rebecca as she works in the lovely garden of her strict Aunt Miranda while letting her imagination run wild with poetic thoughts. Amidst her chores, she contemplates the beauty of nature and the challenges of writing, which she always wants to perfect. The narrative captures her longing for freedom and adventure, alongside her youthful innocence and curiosity. As the story unfolds, a significant event disrupts the tranquility of Riverboro: the death of a woman leads Rebecca to reflect on themes of life and loss, revealing her sensitive nature and desire to make a difference for others, particularly for a small orphaned child. (This is an automatically generated summary.)s
Jack o' Lantern -- Daughters of Zion -- Rebecca's thought book -- A tragedy in millinery -- The saving of the colors -- The state o' Maine girl -- The little prophet -- Abner Simpson's new leaf -- The green isle -- Rebecca's reminiscences -- Abijah the brave and the fair Emmanjane.
Release date is 1998-07-01
Produced by Theresa Armao, and David Widger
Keywords: Domestic fiction; Girls -- Juvenile fiction; Aunts -- Juvenile fiction